Evaluasi Kinerja Proyek pada Proyek Konstruksi Jalan dengan Menggunakan Metode Nilai Hasil - Zetta Rasullia Kamandang (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
The fundamental goal of project management is to finish a facility building project on schedule and within budget while adhering to defined standards and specifications. No matter how great the construction project plan is, if frequent and timely reviews are not done throughout project execution, neither the project progress nor the plan's efficacy can be evaluated. The Earned Value Method (EVM) is one of the tools used in project management that integrates scope, cost and time or schedule measures and provide an accurate picture of current project state at the time of control. This research implements the EVM to road construction project to observe the project performance during its execution and to estimate the cost and the duration of the project completion. Based on the calculation, the project team has efficient performance in using their time and cost for week one until week three, but it decreased especially in time of execution (0,864 of SPI value). Further calculations predict the project needs to prepare Rp. 115.935.300,00 to finish with Rp. 264.828.113,00 of total cost while the TE value shows this project will be finished one week behind its initial planning if no corrective action is done.